2019
DOI: 10.5114/wiitm.2019.81439
|View full text |Cite
|
Sign up to set email alerts
|

Urology resident training in laparoscopic surgery - results of the first national survey in Poland.

Abstract: IntroductionFor many urological procedures the open approach is being replaced by the laparoscopic approach. Laparoscopy technique requires special training conditions. A well-designed, step-by step training program is significantly important for shortening the learning curve.AimThe purpose of the study was to evaluate urology residents’ (UR) experience in laparoscopic procedures, training patterns and facilities available in departments of urology in Poland.Material and methodsThe survey developed by the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…While technical skills can be acquired by practice, a mentor's role is to impart critical nontechnical skills necessary to overcome laparoscopic surgery's learning curve and guide the trainee through his mistakes during the initial learning phase. 15 Operating in a fellow urologist's presence is also helpful, with the benefits of both surgeons' combined experiences and increased operating surgeon's confidence. The best mentors are often our own mistakes, and we advocate watching recorded operative videos for all cases to identify and correct the past inaccuracies.…”
Section: Discussionmentioning
confidence: 99%
“…While technical skills can be acquired by practice, a mentor's role is to impart critical nontechnical skills necessary to overcome laparoscopic surgery's learning curve and guide the trainee through his mistakes during the initial learning phase. 15 Operating in a fellow urologist's presence is also helpful, with the benefits of both surgeons' combined experiences and increased operating surgeon's confidence. The best mentors are often our own mistakes, and we advocate watching recorded operative videos for all cases to identify and correct the past inaccuracies.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the patient receives personalized treatment, and the learning curve related to the particular method is a part of this course. Hence, we believe that an “experience-related learning curve” is more appropriate [ 17 , 18 ], so the learning curve could be shorter in experienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…It is also widely believed that it should only be performed by surgeons with advanced skills in minimally invasive surgery [ 31 ]. In another study, it was reported that the laparoscopic skills of surgeons who had access to laparoscopic training were more satisfactory [ 32 ]. In particular, making laparoscopic courses a part of education is important for reducing surgeons’ concerns.…”
Section: Discussionmentioning
confidence: 99%